The early years of television and the BBC - Medhurst, Jamie (Edinburgh University Press, 2022)
"The British journalist C. P. Scott once said of television, 'Not a nice word. Greek and Latin mixed. Clumsy.' From its earliest days, when people began to discover ways of 'seeing at a distance' through to the multi-platform media environment of today, television has shown itself to be a resilient and adaptable method of communication. Based on detailed archival research, The Early Years of Television and the BBC explores the relationship between the BBC and television from the mid-1920s through to the outbreak of the Second World War. Jamie Medhurst provides an account of the oft-forgotten 30-line television service (1932-5) and re-evaluates the belief that Sir John Reith, the Corporation's Director-General until 1938, would have nothing to do with television."-- Provided by publisher.
Keywords: British Broadcasting Corporation -- History.; British Broadcasting Corporation; Television broadcasting -- Great Britain -- History.; HISTORY / Europe / Great Britain; Television broadcasting; Great Britain; Business & Economics; History